2014
DOI: 10.1007/s10620-014-3460-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of C-Reactive Protein Levels in Predicting Responsiveness to Iron Therapy in Patients with Inflammatory Bowel Disease and Iron Deficiency Anemia

Abstract: BackgroundIron deficiency anemia (IDA) is a common complication of inflammatory bowel disease (IBD). In clinical practice, many patients receive initial treatment with iron tablets although intravenous (i.v.) iron supplementation is often preferable.AimThis study investigated whether systemic inflammation at initiation of treatment (assessed by C-reactive protein [CRP] and interleukin-6 [IL-6] measurements) predicts response to iron therapy.MethodsData from a previously published phase III trial were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
(52 reference statements)
3
27
0
6
Order By: Relevance
“…Indeed, raised CRP levels have been suggested as a marker for patients who may benefit from first-line intravenous iron therapy. 10 As we stated, almost all adverse events were minor. Our own safety analysis found that all four intravenous compounds were safe (and indeed, effective), as stated in our conclusion.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Indeed, raised CRP levels have been suggested as a marker for patients who may benefit from first-line intravenous iron therapy. 10 As we stated, almost all adverse events were minor. Our own safety analysis found that all four intravenous compounds were safe (and indeed, effective), as stated in our conclusion.…”
mentioning
confidence: 75%
“…Aksan that we should be cautious about applying rank probabilities to important decision-making, 10 and that further head-to-head efficacy and safety trials are needed. Meanwhile, the intravenous preparation selected in most centres will be guided mainly by its local cost, convenience of administration and individual patients' tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested a link between iron deficiency and thrombocytosis in non-CKD patients. 9,21,22 Furthermore, ESA dose was one of the independent determinants of TSAT, and vice versa. 23 Also, ESA-associated venous thromboembolism could be caused by iron-restricted erythropoiesis and would be countered by iron supplementation in non-CKD patients.…”
Section: Discussionmentioning
confidence: 97%
“…ECCO recommends up to 100 mg/day elemental Fe as oral iron for patients with mild anaemia and inactive IBD. 1 Patients with active disease, evidenced by markedly raised CRP levels, tend to respond poorly to oral iron, 7,8 and like those intolerant of oral iron or having Hb <100 g/L, should usually proceed directly to intravenous iron.…”
mentioning
confidence: 99%